Visual Search in the Real World: Color Vision Deficiency Affects Peripheral Guidance, but Leaves Foveal Verification Largely Unaffected - Kugler, Günter; 't Hart, Bernard M.; Kohlbecher, Stefan; Bartl, Klaus; Schumann, Frank; Einhäuser, Wolfgang; Schneider, Erich (Frontiers in Human Neuroscience, 2015)
Background: People with color vision deficiencies report numerous limitations in daily life. However, they use basic color terms systematically and in a similar manner as people with people with normal color vision. We hypothesize that a possible explanation for this discrepancy between color perception and behavioral consequences might be found in the gaze behavior of people with color vision deficiency. Methods: A group of participants with color vision deficiencies and a control group performed several search tasks in a naturalistic setting on a lawn. Results: Search performance was similar in both groups in a color-unrelated search task as well as in a search for yellow targets. While searching for red targets, color vision deficient participants exhibited a strongly degraded performance. This was closely matched by the number of fixations on red objects shown by the two groups. Importantly, once they fixated a target, participants with color vision deficiencies exhibited only few identification errors. Conclusions: Participants with color vision deficiencies are not able to enhance their search for red targets on a (green) lawn by an efficient guiding mechanism. The data indicate that the impaired guiding is the main influence on search performance, while foveal identification (verification) largely unaffected.